Ergonomics Analysis for Angiography Arm Board Design - bin Hidzir Pauzi, Nabill; Azlina binti Mohd Salleh, Noor; Azam Abdullah, Shahrul; Rizwal Ismail, Johan (International Journal of Engineering and Technology, 2018)
Ergonomics is a process of arranging products, process and systems of the design to fit the people involved with them. For this project, the ergonomics is focusing on shoulder abduction movement for the angiography arm board design. Angiography arm board is an arm resting for peripheral angiogram patients. The shoulder abduction is one of the most crucial ergonomic aspects during the angiography procedure. The aim is to prove the ergonomics standard guide and gaining the best posture for the angiography arm board user. In this project, the arm board design and human model are used in Kinovea software. This software is commonly used for workplace and athlete ergonomics analysis. Besides that, ergonomic standard for shoulder abduction are used as a guide which is concise in a 3 zone from safe to dangerous; 0o to 13o (Green zone), 14o to 37o (Yellow zone) and 38o to 67o (Red zone). The result shows that ergonomic aspect is important for the patient because the angiography procedure can take up to an hour or more. Because of that, neglecting the ergonomic aspect may lead to injuries to the joint or Musculoskeletal Disorders (MSDs). From the simulation, the minimum and maximum angle are 17o and 47o respectively. The arm board maximum angle reaches the danger zone, but can be prevented with adjustment and proper placement. For human analysis, a marking at shoulder and hand part is placed to ease the software detect the movement. The human model analysis is to prove the ergonomics standard. The human analysis is proven with shoulder dislocation in minor changes of 2.65 mm in the green zone. The result gained for yellow zone is 5.03 mm difference from initial which is safe but may lead to discomfort and 12.96 mm difference from initial is gained with red zone.
Keywords: Ergonomics; Angiography Arm Board; Human model; Abduction movement.